PELATIHAN ME-RETROFIT RUMAH SEDERHANA DENGAN TEKNOLOGI FEROSEMEN BAGI TUKANG BANGUNAN DI KABUPATEN JEMBER - Amri Gunasti; Muhtar Muhtar; Abadi Sanosra (Universitas Mataram, 2023)
Jember Regency is one of the regencies prone to earthquakes. This disaster has caused a number of damaged buildings in various affected areas. The buildings affected by the earthquake were simple houses built by village builders. They generally do not understand how earthquake shear forces behave in the houses they build. The objective of this activity was to provide the masons with the skills to retrofit simple houses made of unreinforced masonry walls by applying ferrocement technology so that the bearing capacity against earthquake-induced shear forces would be higher. The ferrocement training was conducted in Sukogidri Village, Ledokombo, Jember. This activity was carried out by socialising and coordinating, providing training, conducting group strengthening and evaluation. The average score obtained by individual builders during the pretest was between 39.7 and 40.1. After the training, the average score of personal builders was between 77.6 and 80.3. The overall ability of builders before the training activities was 40.03. The overall ability of the builders after the training was 78.77. The increase in the average ability of builders personally when compared between before and after training with a value between 37.4 to 40.3. Meanwhile, the overall improvement of the builders after the Community Partnership Empowerment (PKM) programme was 38.75. This indicates that the training was very appropriate to improve the ability of builders to apply ferrocement technology to retrofit simple earthquake-damaged houses.